2001
DOI: 10.1111/1468-5884.00175
|View full text |Cite
|
Sign up to set email alerts
|

Consumer evaluation of net utility: Effects of competition on consumer brand selection processes

Abstract: This study explores how brand-related information is integrated within a competitive environment. Specifically, we develop a structural equation model of competition between two brands, which includes each brand's price-quality characteristics (i.e., net utility). The model simultaneously tests how the net utility of the focal and competing brands affects consumers' attitudes, intentions, and choice regarding the focal brand. This study extends existing research with the findings that price-quality evaluations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…Symbolic benefits associated with value focus on the idea that a brand offers benefits beyond that of a product (Hsieh, 2002;Lassar et al, 1995), a brand may be of value because it can be used by customers for self expression (Johar and Sirgy, 1991;Chandon et al, 2000), to enable a customer to be recognized among peers (Childers and Rao, 1992;Goldsmith, Clark and Zboja, 2007) to maintain/enhance their self-esteem (Bhat and Reddy, 1998), or for entertainment or exploration purposes (Chandon et al, 2000). The symbolic viewpoint suggests that a customer may value a brand on the basis of meaning and symbolism associated with and created by community members (Belk 1988;Hsieh, 2002;Laroche, Teng and Kalamas, 2001;Lassar et al, 1995) and through the process of enculturation, according to semiotic theory (Mick, 1986), some customers will construct a priority among the signs, symbols, words and pictures associated with brands and co-construct brand meaning (Kates, 2000; and on that basis, such customers will value the brand.…”
Section: Overview Of Literature On the Idiosyncratic Nature Of Brand mentioning
confidence: 99%
“…Symbolic benefits associated with value focus on the idea that a brand offers benefits beyond that of a product (Hsieh, 2002;Lassar et al, 1995), a brand may be of value because it can be used by customers for self expression (Johar and Sirgy, 1991;Chandon et al, 2000), to enable a customer to be recognized among peers (Childers and Rao, 1992;Goldsmith, Clark and Zboja, 2007) to maintain/enhance their self-esteem (Bhat and Reddy, 1998), or for entertainment or exploration purposes (Chandon et al, 2000). The symbolic viewpoint suggests that a customer may value a brand on the basis of meaning and symbolism associated with and created by community members (Belk 1988;Hsieh, 2002;Laroche, Teng and Kalamas, 2001;Lassar et al, 1995) and through the process of enculturation, according to semiotic theory (Mick, 1986), some customers will construct a priority among the signs, symbols, words and pictures associated with brands and co-construct brand meaning (Kates, 2000; and on that basis, such customers will value the brand.…”
Section: Overview Of Literature On the Idiosyncratic Nature Of Brand mentioning
confidence: 99%
“…With Coke and Pepsi as the brands of choice, the authors found dramatic improvements in predictive power over the single effects model. In all subsequent tests of the extended competitive vulnerability model or parts thereof, Laroche and his colleagues used multiple product and service brands, and different analytical techniques such as regression analysis (e.g., Laroche and Brisoux, 1989;Laroche and Sadokierski, 1994) and structural equation modeling (e.g., Laroche et al, , 1995Laroche et al, , 1996Laroche et al, , 2001. Piece by piece they developed different models that eventually led to the all-encompassing extended competitive vulnerability model.…”
Section: Competition In the Consideration Setmentioning
confidence: 99%
“…To shed light on the matter, we turn to the extended competitive vulnerability model (Laroche, 2002), which suggests that competition takes place throughout the decision-making process. In repeated tests of the model, researchers have found that consumers have positive (negative) attitudes, confidence levels, and purchase intentions vis-à-vis a focal (competing) brand(s) (e.g., Laroche et al, 2001;Laroche et al, in press). Applying the extended competitive vulnerability model in a promotions setting and relying on the existence of direct and cross-advertising effects, we posit the following:…”
Section: Coupons and Competition In The Consideration Setmentioning
confidence: 99%
See 1 more Smart Citation
“…En cuanto a las variables que intervienen en un proceso de elección de marca, son el precio y la calidad, los principales antecedentes de dicha actitud de elección. Así, se asume que en el proceso de elección de un producto, el consumidor determina la utilidad neta al realizar una estimación de estas variables y luego selecciona la marca con la mayor utilidad (Laroche & Kalamas, 2001).…”
Section: Dimensiones De La Motivación Comercial Hedónica Y Utilitariaunclassified